Arranjos produtivos locais de Sergipe : caracterização, política e articulação comercial - Jesus, Daniela Regina Santos de (2010)
Throughout the 20th century the development model adopted in Brazil was characterized by the concentration of income in space and personal terms, resulting in the formation of a society with one of the highest rates of inequality in the world. Lately, in view of the need to correct the problems created by the income concentration, countries in development like Brazil have adopted the new model of endogenous regional development, which proposes alternatives for the elaboration of a new regional development policy for the country. To do so, takes into account the importance of local dimension and relations between the agents in the production process and prioritize the implementation of policies for Local Productive Arrangements - LPAs, whose focus of its economy is based on cooperation, knowledge and learning. Given this context, the present study starts with a mapping of existing LPAs in Sergipe devoted to the promotion of public and private policies in support of these arrangements, in order to present the context in which the state is. Furthermore, were analyzed the data of commercial balance (interstate/international) of Sergipe in order to demonstrate the proximity between these arrangements and the economic performance of the state. Finally, we come to the conclusion that it is possible to generate gains from competitiveness for the less developed regions through the creation of opportunities for small businesses by stimulating the growth of LPAs, the establishment of productive competitive chains and reduce of economy inequalities and social inclusion. .